Strategic management of information and communication technology : the United States Air Force experience with Y2K - Haselkorn, Mark P. (National Academies Press, 2007)
Although Y2K did not result in major disruptions, the event is a rich source of critical lessons for strategic management of information and communication technology (ICT), many of which apply to large organizations today. Using a case study approach, this report describes lessons learned from the response of the Air Force to Y2K and makes recommendations for managing ICT complexity, aligning organizational and ICT strategies, and minimizing risk.